Cyclic poly(l-lactide)s via ring-expansion polymerizations catalysed by 2, 2-dibutyl-2-stanna-1, 3-dithiolane. Issue 9 (8th February 2017) - Kricheldorf, H. R.; Weidner, S. M.; Scheliga, F.
Abstract : l -Lactide was polymerized in bulk at 120 or 160 °C with a cyclic dibutyltin catalyst derived from 1, 2-dimercaptoethane. Abstract : l -Lactides were polymerized in bulk at 120 or 160 °C with cyclic dibutyltin catalysts derived from 1, 2-dimercaptoethane or 2-mercaptoethanol. Only linear chains having one benzyl ester and one OH-end group were obtained when benzyl alcohol was added. Whenl -lactides were polymerized with neat dibutyl-2-stanna-1, 3-dithiolane, exclusively cyclic polylactides were formed even at 120 °C. The temperature, time and monomer/catalyst ratio (M/C) were varied. These results are best explained by a combination of ring-expansion polymerization and ring-extrusion of cyclic oligo- or polylactides with elimination of the cyclic catalyst. Neither syntheses of linear polylactides nor of cyclic lactides involved racemization up to 20 h at 160 °C.